Initiation of modern-style plate tectonics recorded in Mesoarchean marine chemical sediments. (15th July 2017) - Satkoski, Aaron M.; Fralick, Philip; Beard, Brian L.; Johnson, Clark M.
Abstract: The chemistry of the oceans in part reflects a balance between inputs from the continents and mantle. Traditionally, it has been thought that Archean ocean chemistry was dominated by mantle sources, but recent work has suggested that continental weathering during the Archean provided a much higher flux to the oceans than previously recognized. Here, we present new Rb-Sr and Sm-Nd isotope compositions on carbonate (dolomite and limestone) from the 2.94 Ga Red Lake and 2.80 Ga Steep Rock groups in the Superior Province, Canada to assess the potential impact continental weathering had on ocean chemistry during the Mesoarchean, a time when initiation of modern-style plate tectonics has been proposed to have occurred. The low Rb contents of all carbonate samples suggest that clastic contamination does not affect the Sr isotope compositions. Using O and Sr isotope modeling, we identified unaltered samples and estimate a 87 Sr/ 86 Sr ratio of 0.70173 for seawater at 2.94 Ga and 0.70182 at 2.80 Ga. Strontium isotope compositions from both Red Lake and Steep Rock indicate that seawater was significantly more radiogenic than contemporaneous mantle, and suggests that weathering of evolved continental crust was an important input to seawater. Continental weathering likely affected seawater chemistry through uplift of continental lithosphere during the initiation of modern-style plate tectonics at 3.2 Ga, a model that is contrary to those that suggest the Archean continents were small in extent and largely submerged. Initiation of modern-style plate tectonics and associated continental weathering had an important effect on the biosphere, including increased nutrient delivery, as well as creation of ecological niches that allowed development of the first biologically produced shallow marine redox gradients.